2014
DOI: 10.1128/aac.01792-13
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Multidrug-Resistant Mycobacterium tuberculosis Isolates from China

Abstract: eTo investigate the molecular characterization of multidrug-resistant tuberculosis (MDR-TB) isolates from China and the association of specific mutations conferring drug resistance with strains of different genotypes, we performed spoligotyping and sequenced nine loci (katG, inhA, the oxyR-ahpC intergenic region, rpoB, tlyA, eis, rrs, gyrA, and gyrB) for 128 MDR-TB isolates. Our results showed that 108 isolates (84.4%) were Beijing family strains, 64 (59.3%) of which were identified as modern Beijing strains. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
27
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 53 publications
12
27
5
Order By: Relevance
“…Accordingly, 63.8% and 32.8% of XDR-TB isolates in the current study harboured mutations in katG and inhA, respectively. The combination of mutations in katG and inhA promoter region could detect 81.0% of INH resistance among XDR-TB isolates, which is similar to previous data from China [8,12]. In addition, four XDR-TB isolates (6.9%) carried single mutations only in the A(-8)G of oxyR-ahpC AGC → AAC Ser315Asn 4 (6.9) [4,7,8,[12][13][14][15].…”
Section: Discussionsupporting
confidence: 85%
“…Accordingly, 63.8% and 32.8% of XDR-TB isolates in the current study harboured mutations in katG and inhA, respectively. The combination of mutations in katG and inhA promoter region could detect 81.0% of INH resistance among XDR-TB isolates, which is similar to previous data from China [8,12]. In addition, four XDR-TB isolates (6.9%) carried single mutations only in the A(-8)G of oxyR-ahpC AGC → AAC Ser315Asn 4 (6.9) [4,7,8,[12][13][14][15].…”
Section: Discussionsupporting
confidence: 85%
“…DNA sequencing of the hot spot regions in genetic loci demonstrated that the frequency of mutations occurring among INHresistant isolates was 78.7%, similar to the results reported in Jiangxi (19) but lower than the data from Fujian and Shanghai, China. For the RIF-resistant isolates in China, substantial proportions (90.2% to 97.2%) of mutations within the rpoB gene were observed (19)(20)(21)(22)(23)(24)(25). Our results showed that 87.0% of the RIF-resistant isolates carried mutations in the rpoB gene.…”
Section: Discussionmentioning
confidence: 52%
“…Also, the frequency of 62.8% for S531L (rpoB) found in this work was consistent with other studies, considering that published rates range between 40.1% and 82.4%. [31][32][33][34] In the same way, H526D (rpoB) polymorphism, with a found frequency of 7% in this work amply oscillates worldwide, with values ranging from 5.9% to 40%. 31,34 Therefore, great frequency variations are evident between countries, making it necessary to study locally the prevalence of the canonical mutations for each geographical region in order to figure out which polymorphisms have the best predictive accuracy.…”
Section: Discussionmentioning
confidence: 89%
“…[31][32][33][34] In the same way, H526D (rpoB) polymorphism, with a found frequency of 7% in this work amply oscillates worldwide, with values ranging from 5.9% to 40%. 31,34 Therefore, great frequency variations are evident between countries, making it necessary to study locally the prevalence of the canonical mutations for each geographical region in order to figure out which polymorphisms have the best predictive accuracy. As early diagnosis is the best strategy to control MDRTB, several molecular methods to detect drug resistance in M. tuberculosis are currently widely employed.…”
Section: Discussionmentioning
confidence: 89%